Safety Evaluation of α-Lipoic Acid Supplementation: A Systematic Review and Meta-Analysis of Randomized Placebo-Controlled Clinical Studies - Fogacci, Federica; Rizzo, Manfredi; Krogager, Christoffer; Kennedy, Cormac; Georges, Coralie M G; Knežević, Tamara; Liberopoulos, Evangelos; Vallée, Alexandre; Pérez-Martínez, Pablo; Wenstedt, Eliane F E; Šatrauskienė, Agnė; Vrablík, Michal; et al. (Antioxidants (Basel, Switzerland), 2020)
Alpha-lipoic acid (ALA) is a natural short-chain fatty acid that has attracted great attention in recent years as an antioxidant molecule. However, some concerns have been recently raised regarding its safety profile. To address the issue, we aimed to assess ALA safety profile through a systematic review of the literature and a meta-analysis of the available randomized placebo-controlled clinical studies. The literature search included EMBASE, PubMed Medline, SCOPUS, Google Scholar, and ISI Web of Science by Clarivate databases up to 15th August 2020. Data were pooled from 71 clinical studies, comprising 155 treatment arms, which included 4749 subjects with 2558 subjects treated with ALA and 2294 assigned to placebo. A meta-analysis of extracted data suggested that supplementation with ALA was not associated with an increased risk of any treatment-emergent adverse event (all p > 0.05). ALA supplementation was safe, even in subsets of studies categorized according to smoking habit, cardiovascular disease, presence of diabetes, pregnancy status, neurological disorders, rheumatic affections, severe renal impairment, and status of children/adolescents at baseline.
Keywords: α-lipoic acid; safety; dietary supplement; thioctic acid; meta-analysis